Taira no Atsumori or melancholic ahimsha as “cold steel” - Cid Lucas, Fernando (Revista de Artes Marciales Asiáticas, 2012)
In this article we will examine the personality of one of the most important characters in Heike monogatari, the young samurai Taira no Atsumori, and his view of the war and the trade of warrior. Likewise, we will focus on how this historic character is portrayed in some Noh plays, in which his tormented soul refused epics chants and honors achieved in the battlefield, in the search of its eternal rest through religious path.